Case Study of Decreasing of Quality of Processed Waste at Sewage Treatment Plant to Contain Waste Disposal on Ship Mv. Ck Angie - A. Pasaribu, Charry; Yando, Markus; P, Damoyanto (Green Publisher, 2023)
Prevention of contamination by sewage on ships can be overcome by using an auxiliary sewage treatment plant, a sewage treatment plant is a liquid waste treatment installation which is generally intended for domestic waste in the form of feces and laundry residue containing detergents which are harmful to the environment by utilizing aerobic bacteria as waste decomposers and UV sterilizers as a neutralizer for waste parameters. However, in reality when the author and engineer 3 conducted regular tests on the processed water content of the sewage treatment plant from May 4 2021 to May 25 2021, the results of the waste parameters were not in accordance with the manual book. So, according to the test results above, the authors take 3 causes for the decline in the quality of processed water which is the background for writing this thesis, namely the operation of the aeration blower is ineffective, the UV sterilizer does not function properly and the accumulation of sludge or excessive solid residue in the separation tank section. The research method used is descriptive. The approach method used is a qualitative approach method with data collection techniques carried out by means of observation and documentation based on data analysis techniques carried out using root cause analysis (RCA) techniques carried out on the MV ship. CK ANGIE from 11 December 2020 to 24 January 2022. the operation of the aeration blower is ineffective, If the uv sterilizer does not function properly, the cause of the problem is the dirty blower air filter and dirty blower air inlet pipe and the uv sterilizer section is caused by the life of the uv lamp which has exceeded running hours and the uv jacket is dirty. And for engine cadets to pay attention to the exhaust air pressure from the aeration blower so that when the exhaust air pressure from the aeration blower starts to decrease, they can immediately report it to the engineer in charge. suggestions for maintaining the performance of the UV Sterilizer are to pay more attention to the usage period or running hours of the UV Lamp so that the effectiveness of the UV Lamp continues to function properly. And for the jacket section of the UV sterilizer to be cleaned regularly by implementing a regular planned maintenance system (PMS)..